Colocar o sistema financeiro ao serviço dos pobres e das PME - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
O esforço de inclusão financeira alcançou resultados positivos, tendo a bancarização da população moçambicana aumentado consideravelmente, em particular depois de 2011-12. Contudo, o impacto económico e social foi limitado, considerando que a produtividade agrícola se tem mantido baixa e os níveis de pobreza ainda são elevados. A doutrina neoliberal na esfera económica, a sua expressão nas políticas monetárias restritivas e a fraqueza do sistema de democracia multipartidária têm sido factores institucionais de constrangimento ao desenvolvimento económico e social. Consequentemente, este estudo propõe algumas medidas de reforma institucional para se expandir o crédito aos agricultores familiares de subsistência, às pequenas e médias empresas, à população em geral e às famílias de rendimento mais baixo em particular. Os jovens poderão beneficiar de créditos mais acessíveis para habitação. Os produtores familiares rurais também necessitam de um suporte sistémico público.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Putting the financial system to work for the poor and SMEs - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
Abstract: The financial inclusion effort achieved positive results, with the number of Mozambicans having access to banking services increasing considerably, particularly after 2011–12. However, the economic and social impact was limited, considering that farm productivity has remained low and poverty levels are still high. The neoliberal doctrine in the economic sphere, its expression in the restrictive monetary policies, and the weakness of the multi-party democracy system have been institutional factors restricting economic and social development. Consequently, this study proposes some institutional reform measures to expand credit to family subsistence farmers, small and medium-sized enterprises, the population in general, and low-income families in particular. Young people could benefit from more accessible housing loans. Rural family farmers also need systemic, public support.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Os Desafios da Expansão do Ensino Superior e a Formação do Capital Humano em Moçambique - Batone, Domingos Carlos (2020)
This research entitled “The Challenges of Expanding Higher Education and the Formation of Human Capital in Mozambique”, analyzes the quality, sustainability and democratization of Higher Education and its influence on the development of human capital. However, the results of this study show that despite the increase in the number of Universities, in several developing countries, such as Mozambique, many of the poorest people remain in the rural sector and tend to continue there for several decades, with the need to bring establishments closer together teaching communities. To reduce poverty, it is necessary to do something for this sector, the right thing to do is to educate the population until reaching a higher level and generate human capital. Based on the consulted literature, using bibliographic research, documentary research and relying on the Human Capital Theory, it was found that the experiences of successful countries depended on social stability, and this cannot be maintained when large portions of the population fall behind in education. Therefore, higher education in these areas cannot be just a way out, it must also be a way of ascending life to obtain more income and consequently foster development. In this sense, the conclusion was reached that higher education is the best way to reduce social inequalities and poverty in Mozambique, however, the sustainability, quality and democracy of higher education must be preserved.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; education / educação; poverty / pobreza; youth / juventude

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, João, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social